2015
DOI: 10.1149/2.0671514jes
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Charge Storage in Thin Films of MnO2Derived by Electrochemical Oxidation of MnO Atomic Layer Deposition Films

Abstract: Sodium charge storage in ultrathin MnO2 films was studied using cyclic voltammetry (CV) and electrochemical quartz crystal microbalance (EQCM) measurements. The MnO2 films were fabricated by electrochemical oxidation of MnO films grown by atomic layer deposition (ALD). CV analysis confirmed that oxidation of MnO to MnO2 involved two moles of electrons per mole of Mn in the MnO ALD film. Scanning electron microscopy (SEM) images revealed that electrochemical oxidation of MnO led to the formation of MnO2 nanoshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 51 publications
7
62
0
Order By: Relevance
“…The CV of CNTs/MnO 2 in 1‐M Na 2 SO 4 electrolyte displayed shape without redox peaks, demonstrating pseudocapacitive behavior with fast and reversible surface reactions indicating good capacitive characteristics . However, the CV curve of the supercapacitor based on CNTs/MnO 2 in 1‐M H 2 SO 4 electrolyte revealed shapes with one pair of noteworthy redox peaks appearing at around 0.24 V (cathodic) and 0.6 V (anodic), typical behavior of the integration of the EDLC of CNTs and the pseudocapacitance of MnO 2 . Additionally, the area of the CV loop of CNTs sheet is much smaller than that of CNTs/MnO 2 composite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CV of CNTs/MnO 2 in 1‐M Na 2 SO 4 electrolyte displayed shape without redox peaks, demonstrating pseudocapacitive behavior with fast and reversible surface reactions indicating good capacitive characteristics . However, the CV curve of the supercapacitor based on CNTs/MnO 2 in 1‐M H 2 SO 4 electrolyte revealed shapes with one pair of noteworthy redox peaks appearing at around 0.24 V (cathodic) and 0.6 V (anodic), typical behavior of the integration of the EDLC of CNTs and the pseudocapacitance of MnO 2 . Additionally, the area of the CV loop of CNTs sheet is much smaller than that of CNTs/MnO 2 composite.…”
Section: Resultsmentioning
confidence: 99%
“…This process is also transferred to the charge‐discharge curves at low scan rates (5 and 10 mV/s) because these curves have no sawtooth shape due to solubility of MnO 2 . The higher capacitance than the theoretical value (1370 F/g) (especially for low scan rates) is linked to reversible redox reactions due to solubility of MnO 2 in solution and accompanied by the insertion/deinsertion of alkali Na + cation or H + protons from the electrolyte . It is then recommended to use Na 2 SO 4 as electrolyte to minimize the dissolution of MnO 2 film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups found that preinsertion of cations (such as Na + and K + ) in MnO 2 can effectively improve supercapacitive performance. [25] In most of previous works on cation preinserted MnO 2 , the cation content is low and the cation/Mn atomic ratio is usually less than 0.3, [26,27] which limits pseudocapacitance contribution from MnO 2 . [25] In most of previous works on cation preinserted MnO 2 , the cation content is low and the cation/Mn atomic ratio is usually less than 0.3, [26,27] which limits pseudocapacitance contribution from MnO 2 .…”
Section: Doi: 101002/adma201700804mentioning
confidence: 99%
“…The fraction of diffusive charge storage, f d , is determined using the expression to separate capacitive and diffusive charge storage using expressions of current versus sweep rate, [40,41] as described in more detail in the Supporting Information of ref. [14].…”
Section: Deconvolution Of Capacitive and Diffusive Charge Storagementioning
confidence: 99%